2018
DOI: 10.1155/2018/5845491
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Like Effects of Gyejibokryeong-hwan in a Mouse Model of Reserpine-Induced Depression

Abstract: Treatment with the antihypertensive agent reserpine depletes monoamine levels, resulting in depression. In the present study, we evaluated the antidepressant effects of Gyejibokryeong-hwan (GBH), a traditional Korean medicine, in a mouse model of reserpine-induced depression. Mice were treated with reserpine (0.5 mg·kg−1, i.p.) or phosphate-buffered saline (PBS, i.p., normal) once daily for 10 days. GBH (50, 100, 300, and 500 mg·kg−1), PBS (normal, control), fluoxetine (FXT, 20 mg·kg−1), or amitriptyline (AMT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…Animals treated with reserpine showed sagging, decreased body temperature, and tonic symptoms (Antkiewicz-Michaluk et al, 2014), which were treated with tricyclic antidepressants and monoamine oxidase inhibitors and can antagonize the symptoms of upper eye sagging and body temperature decrease. Studies have found that reserpine is widely used in the modeling of depression, Parkinson's disease and schizophrenia (Fernandes et al, 2012;Park et al, 2018). The reserpine-induced depression rat model can be divided into two types, one for a low dose (i.p., 0.1-0.5 mg/kg) and one for a single high dose (i.p., 1-5 mg/kg) (Fernandes et al, 2012;Ozerov et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Animals treated with reserpine showed sagging, decreased body temperature, and tonic symptoms (Antkiewicz-Michaluk et al, 2014), which were treated with tricyclic antidepressants and monoamine oxidase inhibitors and can antagonize the symptoms of upper eye sagging and body temperature decrease. Studies have found that reserpine is widely used in the modeling of depression, Parkinson's disease and schizophrenia (Fernandes et al, 2012;Park et al, 2018). The reserpine-induced depression rat model can be divided into two types, one for a low dose (i.p., 0.1-0.5 mg/kg) and one for a single high dose (i.p., 1-5 mg/kg) (Fernandes et al, 2012;Ozerov et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study conducted by our group, GBH was shown to exhibit antineuroinflammation effects in the hippocampus of a mouse model of reserpine-induced depression [19]. Several studies have reported that microglia regulate hippocampal neurogenesis in neurodegeneration [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…73 This is a result of its role in inhibiting membrane enzymatic activities such as glucosyltransferase and on the other hand by activating autolytic enzymes in the pathogen cell wall and this leads to a disorganization of the membrane phospholipids bilayer, which may result in a notable decrease in nutrient uptake, the inhibition of bacterial cell growth, and an increase in membrane permeability and cell lysis. 74 The fatty acids found in Opuntia ficus indica seed oil are linoleic acid as the major fatty acid (61.01%), followed by oleic (25.52%) and palmitic (12.23%) acids. Both myristic, stearic and arachidonic acids were detected in low amounts.…”
Section: Figure 3: Chemical Structures Of Some Betalainsmentioning
confidence: 99%